Vitamin D supplementation reduces the risk of fall in the vitamin D deficient elderly: An updated meta-analysis. Issue 11 (November 2021) - Ling, Yali; Xu, Feng; Xia, Xuedi; Dai, Dexing; Xiong, An; Sun, Ruoman; Qiu, Lei; Xie, Zhongjian
Summary: Introduction: Vitamin D supplementation has been widely recommended to prevent falls. However, considerable controversy exists regarding the association of such supplementation and fall risk. Previous meta-analyses yielded inconsistent results because of differences in the baseline of 25-hydroxyvitamin D [25(OH)D] and dose of vitamin D and use of vitamin D or in combination with calcium in different studies. Furthermore, some studies published recently were not included in the previous meta-analyses. Therefore, an updated and comprehensive meta-analysis is warranted. Methods: We systematically searched several literature databases including PubMed and the Embase from inception to September 2020. The protocol for this meta-analysis was registered with PROSPERO (CRD42021226380). Randomized clinical trials (RCTs) reporting the effect of vitamin D supplementation alone or with calcium on fall incidence were selected from studies. Qualitative and quantitative information was extracted; the random-effects model was conducted to pool the data for fall; statistical heterogeneity was assessed using the I 2 test and potential for publication bias was assessed qualitatively by a visual estimate of the funnel plot and quantitatively by calculation of the Begg's test and the Egger's test. Results: Of the citations retrieved, 31 eligible studies involving 57 867 participants met inclusion criteria, reporting 17 623 falls. A total of 21 RCTs of vitamin D alone and 10 RCTs of vitamin D plus calcium were included in the meta-analysis. The meta-analysis of 21 RCTs (51 984 participants) of vitamin D supplementation alone (daily or intermittent doses of 400–60 000 IU) did not show a reduced risk of falls (The risk ratio [RR] 1.00, 95% confidence intervals [CI] 0.95 to 1.05) compared to placebo or no treatment. Subgroup analyses showed that the baseline of serum 25(OH)D concentration less than 50 nmol/L resulted in a reduction of fall risk (RR 0.77, 95% CI 0.61 to 0.98). In contrast, the meta-analysis of 10 RCTs (5883 participants) of combined supplementation of vitamin D (daily doses of 700–1000 IU) and calcium (daily doses of 1000–1200 mg) showed a 12% reduction in the risk of fall (RR 0.88, 95% CI 0.80 to 0.97). Conclusions: The combination of vitamin D and calcium have beneficial effects on prevention falls in old adults. Although vitamin D supplementation alone has no effect on fall risk in old adults with 25(OH)D levels higher than 50 nmol/L, vitamin D supplementation alone does have a benefit on prevention of falls in old adults with 25(OH)D levels lower than 50 nmol/L.